2020
DOI: 10.1007/s40475-020-00208-z
|View full text |Cite|
|
Sign up to set email alerts
|

COVID-19: Biosafety in the Intensive Care Unit

Abstract: Purpose of Review COVID-19 is a new, highly transmissible disease to which healthcare workers (HCWs) are exposed, especially in the intensive care unit (ICU). Information related to protection mechanisms is heterogeneous, and the infected HCWs’ number is increasing. This review intends to summarize the current knowledge and practices to protect ICU personnel during the patient management process in the context of the current pandemic. Recent Findings The transmission me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 54 publications
0
7
0
1
Order By: Relevance
“…Although the practice of frequent doffing inside the patient area in the wards might increase the risk of infection, the UK guideline is to use the same mask for a session of work, and the infection rate for HCWs is even higher [8,22]. With other viral infections, contamination while doing D&D has been observed [23], marking the importance of assisted D&D and training [24]. Based on data presented by the authors, only <40% of the participants had been trained in D&D, thus the prevention of possible contamination during D&D needs more attention.…”
Section: Characteristics Infection Rates and Exposure Among Hus Permentioning
confidence: 99%
“…Although the practice of frequent doffing inside the patient area in the wards might increase the risk of infection, the UK guideline is to use the same mask for a session of work, and the infection rate for HCWs is even higher [8,22]. With other viral infections, contamination while doing D&D has been observed [23], marking the importance of assisted D&D and training [24]. Based on data presented by the authors, only <40% of the participants had been trained in D&D, thus the prevention of possible contamination during D&D needs more attention.…”
Section: Characteristics Infection Rates and Exposure Among Hus Permentioning
confidence: 99%
“…In this scoping review, we collected and systemically charted the available literature on PPE-related AEs and identified gaps in the existing knowledge. We found that nurses and other HCWs working in the ICU are at a high risk of infection as aerosol-generating procedures are more frequent (D ıaz-Guio et al, 2020). Moreover, HCWs in the ICU are required to wear PPE in the patient room as well as in the patient area (World Health Organization, 2020).…”
mentioning
confidence: 99%
“…The additional risk of COVID-19 exposure would also likely occur in healthcare workers in the COVID-19 intensive care unit. Physicians performing procedures such as intubation, bronchoscopy and care of patients during a cardiorespiratory arrest are known to be exposed to high viral burdens [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%